Association of tumor necrosis factor‐α ‐308 G/A gene polymorphism with coronary artery diseases: An evidence‐based study. Issue 1 (23rd February 2017) - Kazemi, Elaheh; Jamialahmadi, Khadijeh; Avan, Amir; Mirhafez, Seyed Reza; Mohiti, Javad; Pirhoushiaran, Maryam; Hosseini, Nedasadat; Mohammadi, Akram; Ferns, Gordon A.; Pasdar, Alireza; Ghayour‐Mobarhan, Majid
Abstract : Background: Coronary artery disease (CAD) is the leading cause of death worldwide and remains a major health problem, providing the rationale for identification of molecular markers for detection of individuals at high risk of developing CAD. Tumor necrosis factor‐α (TNF‐α) plays a crucial role in the pathogenesis of CAD. We have therefore explored the association of TNF‐ α 308 (G/A) gene polymorphism in 903 individuals with/without CAD. Methods: TNF‐ α 308 gene polymorphism was analyzed in 903 subjects of whom 222 were healthy controls. Among the 681 patients who were investigated angiographically, 468 had ≧50% stenosis and 213 patients had <50% stenosis. Biochemical profiles (eg, triglycerides, high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol, fasting blood glucose, and CRP) were evaluated. Associations between TNF‐α genotypes with biochemical and anthropometric characteristics were determined. Results: The frequencies of TNF‐ α ‐AA or AG genotypes were significantly lower in patients classified as CAD patients with ≥ or <50% obstruction in at least one coronary artery, compared to the control group. We observed that CAD patients with ≥50% stenosis and with AA genotype were associated with higher risk of CAD with OR of 3.56 (95%CI: 1.02‐12.41; P =.046) using multivariate analysis. Moreover, we found that TNF‐ α ‐308‐AA genotype was associated with blood pressure and CRP level in CAD patients, compared to the wild type‐genotype. Conclusion: Our data showed an association of TNF‐ α ‐308G/A polymorphism with CAD patients with ≥50% obstruction, supporting the need for further investigations on the role of TNF‐ α ‐308G/A polymorphism with hypertension.